Knowledge, attitudes and current practice of specialists and registrars in obstetrics and gynaecology regarding the use of the intrauterine contraceptive devices postpartum - Braam, Natalie Alexandra Louise (My University, 2018)
Introduction: Intrauterine devices (IUD’s) are a reliable long acting form of contraception. The American Congress of Obstetrics and Gynaecology, The WHO, The American College of Obstetrics and Gynaecology and The South African guidelines encourage immediate postpartum insertion of the device. The use of intrauterine devices in South Africa however remains low. The aim of this study was to assess the knowledge, attitude and practice of specialists and registrars in obstetrics and gynaecology with regards to the intrauterine device postpartum. Methods: A descriptive cross sectional study was conducted. It consisted of a self-administered questionnaire. A total of 170 specialists and registrars in South Africa were questioned as to their knowledge, attitude and practice regarding the IUD’s in the postpartum period. Results: Knowledge amongst doctors was good. Of those interviewed, 93.6% (n=147), were aware that you could insert the IUCD in the postpartum period. The IUCD was view favourably by most doctors; however the fear of expulsion was noted to be a barrier to its use. The IUCD is inserted in the postpartum period by 71.2% (n=111) of the doctors questioned. Conclusion: Knowledge in this subgroup of doctors, regarding the IUD in the postpartum period, is good. The attitude towards the IUD postpartum is favourable. Practice however is not reflective of the good knowledge and favourable attitude demonstrated.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine (Obstetrics & Gynaecology). Johannesburg, 2018